The Importance of Integrating Specialized Texts in Andragogical Education for Teaching Uzbek as a Foreign Language - Umurzakova Sevara Abdukarimovna (Periodica Journal, 2025)
This article explores the integration of specialized texts and innovative technologies in the teaching of Uzbek as a foreign language, with a particular focus on adult learners in professional fields such as medicine and law. It examines the use of domainspecific materials—such as medical records and legal contracts— combined with interactive, immersive approaches like gamification, digital feedback mechanisms, and virtual reality to enhance language acquisition. By emphasizing practical application, this study highlights the importance of aligning language education with professional needs, motivating learners through relevant content, and improving their ability to navigate real-world professional scenarios. The article also discusses the role of emerging technologies, such as artificial intelligence and immersive environments, in transforming language education. It concludes with recommendations for future research and the expansion of these methods to broader professional domains, aiming to make language education more relevant and impactful in a globalized world.
Keywords: Uzbek language education; specialized texts; professional language learning